Economic Crises and Inequality: The Case of Bolivia - Antonio N Bojanic (Journal of Developing Economies, 2026)
Objective: This paper examines the impact of three types of economic crises – banking, inflation, and foreign exchange reserves crises – on various indicators of economic inequality in Bolivia. Design/Methods/Approach: The study utilizes a GMM framework and quarterly data spanning from 1960 to 2023. GMM methodology is utilized for several reasons: (i) possible endogeneity of the regressors is overcome using instruments to produce consistent and unbiased estimates; (ii) it does not require the specification of the full distribution of the errors, making GMM estimates more robust; and (iii) it accounts for heteroskedasticity and autocorrelation, common issues in time-series analysis like the one conducted here. Findings: The findings highlight the nuanced effects of these crises: banking and inflation crises generally reduce income inequality, while foreign exchange reserves crises exacerbate it. Specifically, an increased likelihood of a banking crisis is associated with reductions in the Palma ratio, the poverty gap, the Gini coefficient, and the Atkinson and Theil indices, and with improved income shares for the bottom 40 percent. Similar patterns are observed during inflation crises. In contrast, foreign exchange reserve crises lead to higher Palma ratios and poverty gaps, indicating worsening income inequality and rising poverty levels. The study underscores the importance of maintaining robust safety nets to protect vulnerable populations during periods of economic distress. Originality/Value: A key contribution is to highlight the varying impacts of different types of economic crises on income inequality in a developing economy. Practical/Policy implication: From a policy perspective, since all types of crises – banking, inflation, and foreign exchange reserves – are likely to harm long-term growth and stability, the Bolivian government should maintain effective safety nets that support the poor during periods of economic distress.